Hydrogen-stimulated migration of metal atoms in «metal — semiconductor» structures - Matyushin, V. M.; Zhavzharov, E. L. (Technology and design in electronic equipment, 2012)
The article presents experimental results of the effect atomic hydrogen has on the Cu—Ge and Ni—Ge structures. It has been shown experimentally that the treatment of structures at room temperature is accompanied by the introduction of metal atoms with an abnormally high concentration in the surface layers of thickness up to 1 mm.